The transformation of learning culture in the age of AI: a sociological review of education from the perspective of Pierre Bourdieu’s social habitus - Istiqomah, Nisfu; Khasanah , Nur (Priviet Social Sciences Journal, 2026)
The development of artificial intelligence (AI) technology has led to significant changes in students learning. The increasing use of application platforms such as ChatGPT, Gemini, and Meta AI has demonstrated a shift in learning habits, which now emphasize speed and replace the reflective and collaborative approaches that are characteristic of traditional learning. This study aims to analyze how the use of AI can create new social habits among students in Indonesia and its impact on social values, morals, and the education system. This study uses a descriptive qualitative approach with a literature review through the analysis of various relevant scientific literature, both national and international. The results show that the repeated use of AI will form a digital habitus that emphasizes efficiency and quick results but weakens students' critical and reflective thinking skills. Furthermore, unequal access to technology deepens educational stratification, while the values of academic honesty and social responsibility are beginning to shift. Therefore, education in the AI era must focus on strengthening ethical digital literacy and the formation of a reflective habitus to ensure that technological development remains aligned with humanitarian values, morality, and academic integrity.